Polydopamine Modified Activated Carbon for Capacitive Desalination. Issue 12 (1st September 2017) - Xie, Zhengzheng; Cheng, Jian; Yan, Junbin; Cai, Wenshu; Nie, Pengfei; Chan, Henry T. H.; Liu, Jianyun
Abstract : Activated carbon (AC) is one of the most typical carbon materials used for capacitive deionization (CDI) due to its large specific surface area and porous structure. However, the poor water wettability of AC remains a major challenge for CDI application in aqueous solutions. Here, polydopamine (PDA) is facilely modified on AC surface (PDA/AC) via self-polymerization of dopamine to improve its wettability, while the PDA thickness can be conveniently tuned by varying the soak time. X-ray photoelectron spectroscopy (XPS), Energy dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), N2 adsorption and contact angle measurements are taken to characterize the properties of PDA/AC. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analysis indicate that PDA/AC electrodes exhibit an ideal electrochemical double layer capacitive behavior. The salt removal amount of 12 mg/g on PDA/AC with 4 h soaking is achieved during the desalination process, compared to 4.5 mg/g of AC electrode. The PDA/AC electrode is a very promising material for capacitive deionization.